answersLogoWhite

0


Best Answer

a^2b^2c^2

^2 is squared

User Avatar

Wiki User

โˆ™ 2011-03-21 21:17:27
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: What is a squared x b squared x c squared?
Write your answer...
Submit
Related questions

A B and C are all squared numbers. A b also a c and b c make squared numbers what are A B and c?

ab x ac = ab - ac


What is the answer to a x a x a plus b x b x b equals c x c x c?

well it could be anything, but I think you are thinking of Pythagoras' theorem. a(2) x b(2) = c(2) (2) = squared


How do you do pythagorean theorem when you have a and c?

B squared equals c squared minus a squared then to find B take the square root of you answer for b squared


What did Pythagoras do in his life time?

he made the theorem C squared = A squared + B squared and A squared = C squared - B squared or B squared = C squared - A squared


If A squared plus B squared equals C squared and C equals 8 and A and B are the same length what are A and B?

4


What do you do with c squared and b squared to get a squared?

a^2+b^2=c^2a^2=c^2-b^2a=(c^2-b^2)^(1/2)


Is equation for the Pythagorean theorem is a b c?

it is asquared +b squared = c squared


What is (a-b plus c)2?

The Pythagoream Thereom is a^2 + b^2 = c^2. Written out it is a squared plus b squared equals c squared.


What is c assuming a squared b squared c squared and a 3 and b 8 and the answer cannot be in decimals?

c= sq rt of 73


What is the quadratic equasion?

If your Problem is organized like this: A x squared plus B x plus C, the equation is: (B plus or minus the square root of(B squared minus 4 A C)) over 2A


When a squared plus b squared equals c squared what is the square root of the square root of the square root of a squared squared squared plus b squared squared squared?

Since a squared plus b squared equals c squared, that is the same as c equals the square root of a squared plus b squared. This can be taken into squaring and square roots to infinity and still equal c, as long as there is the same number of squaring and square roots in the problem. Since this question asks for a and b squared three times, and also three square roots of a and b both, they equal c. Basically, they cancel each other out.


What is A squared minus B squared?

Same as (A-B)x(A+B)


What is hypothesis theorem?

a squared + b squared = c squared


What is pythagorus theory?

A squared + B squared = C squared


What is the formula for pronumeral?

a squared + b squared = c squared


Why does symmetry occur in quadratic function?

That's related to the fact that, for example, x squared is the same as (-x) squared. Note that any equation of the form "x squared + bx + c = 0", with constants a, b, and c can be rewritten as "(x - d) squared + f = 0", for possibly different constants d and f.


How do you find the length of the leg of a triangle?

if you mean a right triangle then the formula is a squared + b squared = c squared. a and b are the legs and c is the hypotunese. the legs are the smallest number then the hypotenese. An example is a=3 , b= ? and c =5 use the formula : a squared + b squared = c squared 3 squared + b squared = 5 squared 9 + b squared = 25 -9 - 9 _________________________________________ b squared = 16 Then you have to take the squared root of 16 which is 4 and 4 is b squared.


How do you find the pythgorean theorem?

a(squared)+b(squared)=c(squared) The largest number is the c, and you can choose the a and b, since you need to find the a or the b. For example: You have the numbers 3, and 5 and you needed to find b. a(squared+b(squared)=c(squared) 3(squared)+b(squared)=5(squared) 9+b(squared)=25 -9 -9 b(squared)=16 Then take the square root b=4


What are some common math formulas?

Well pythagorus theoreum is a squared plus b squared equals c squared and circumference equals pie x diameter and area equals pie x radius squared


In the pythagorean theorem is b twice of a?

In the Pythagorean Theorem b is not twice a. The formula is [ a squared + b squared = c squared].


What is the equasion for the pothagoream therom?

A squared + B squared = C squared


What is pythagoren theorem?

The pythagorean theorem is a squared + b squared = c squared, where a and b are the legs of a right triangle, and c is the hypotenuse of a right triangle.


What is the pyhtagoream thereom?

The Pythagoream Thereom is a^2 + b^2 = c^2. Written out it is a squared plus b squared equals c squared.


In the vertex form of a quadratic function y equals a the quantity of x-b squared plus c what does the b tell you about the graph?

The standard form of the quadratic function in (x - b)2 + c, has a vertex of (b, c). Thus, b is the units shifted to the right of the y-axis, and c is the units shifted above the x-axis.


What does negative b squared equal to?

It's equal to positive b squared, or (b x b) .